2019
DOI: 10.2478/bjlp-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Purpose of the Contract and the Liability of an Expert Towards a Third Party in Czech, Austrian, and German Private Law

Abstract: The aim of the paper is to describe the so-called protective purpose of the contract, by demonstrating the liability of experts for damage caused by an imperfect expert opinion, incorrect advice, or information. The comparative method will be used in conjunction with analyzing the Czech, Austrian, and German arrangements – their continuities and differences. Criteria for assessing whether this is a protective purpose of the contract and how these criteria vary in different legal frameworks are discussed in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This legal framework provides clear regulations and boundaries for managers' actions, ensuring they comply with legal requirements in fulfilling their duties and exercising their power. Other scholars have suggested that, due to agency problems, the contractual basis of business and law between limited liability companies and managers may have different consequences depending on the purpose of the contract [16]. Due to the special power and obligations of upper management in companies, we must critically and deeply discuss the personal power of top managers.…”
Section: Managerial Myopia Behavior and Enterprise Sustainability Per...mentioning
confidence: 99%
“…This legal framework provides clear regulations and boundaries for managers' actions, ensuring they comply with legal requirements in fulfilling their duties and exercising their power. Other scholars have suggested that, due to agency problems, the contractual basis of business and law between limited liability companies and managers may have different consequences depending on the purpose of the contract [16]. Due to the special power and obligations of upper management in companies, we must critically and deeply discuss the personal power of top managers.…”
Section: Managerial Myopia Behavior and Enterprise Sustainability Per...mentioning
confidence: 99%
“…After these deadlines have expired in vain, the company would not be able to assert these claims in court, because the deadline has a preclusive nature. In practice, this means that the claims would disappear (Matejkova and Pavelek 2019).…”
Section: Non-competitionmentioning
confidence: 99%